The boy who knew too much : an astounding true story of a young boy's past-life memories - Byrd, Cathy, 1976- (Carlsbad, California : Hay House, Inc., 2017)
This is a powerful and inspirational story about a young baseball prodigy who, at the age of two, began sharing vivid memories of being a baseball player in the 1920s and 30s. Christian Haupt described historical facts about Lou Gehrig that he could not have possibly known at the time. Distraught by their son's uncanny revelations, his parents embarked on a sacred journey of discovery that shook their beliefs to the core and forever changed their views on life and death.
Baseball fever -- Babe ruth was mean to you? -- Tall like daddy -- Old souls -- The grudge -- Finding lou gehrig -- Possessed or crazy -- Spring fever -- Take me out to the ball game -- The pitch -- A national treasure -- I just know -- The good doctor comes to town -- Journey to the past -- A mother's love -- Love never dies -- Whispers of the soul -- Baseball heaven -- Pride of the Yankees -- Family heirlooms -- Heaven sent -- Finding mom gehrig -- Stitches.
ENH
Keywords: Haupt, Christian; Haupt, Christian; Reincarnation -- Biography; Baseball -- Miscellanea; Baseball -- Miscellanea; BIOGRAPHY & AUTOBIOGRAPHY -- Personal Memoirs; BODY, MIND & SPIRIT -- Afterlife & Reincarnation; RELIGION -- Spirituality; Reincarnation; Biographies; Biographies; Biography; Biographies